Proteomic analysis of Taenia solium cysticercus and adult stages - Li, Lizhu; He, Wei; Fan, Xianmin; Liu, Meichen; Luo, Bo; Yang, Fengjiao; Jiang, Nan; Wang, Lingjun; Zhou, Biying (Frontiers in Veterinary Science, 2023)
Taenia solium(T. solium) cysticercosis is a neglected parasitic zoonosis that occurs in developing countries. Since T. solium has a complex life cycle that includes eggs, oncospheres, cysticerci, and adults, presumably many proteins are produced that enable them to survive and establish an infection within the host. The objectives of this study were to perform a comparative proteomic analysis of two ontogenetic stages of T. solium (cysticerci and adult) and to analyze their differential expression of proteins. To do this, proteins were separated by High Performance Liquid Chromatography(HPLC) fractionation, and protein samples were also digested in liquid and identified by liquid chromatography tandem mass spectrometry(LC-MS/MS); the differentially expressed proteins were then processed by a bioinformatics analysis and verified by parallel reaction monitoring (PRM). In total, we identified 2481 proteins by label-free quantitative proteomics. Then differentially expressed proteins were screened under P values < 0.05 and 2 fold change, we found that 293 proteins up-regulated and 265 proteins down-regulated. Through the bioinformatics analysis, we analyzed the differences types and functions of proteins in the Taenia solium and cysticercus, the data will provide reference value for studying the pathogenic mechanism of the two stages and the interaction with the host, and also support for further experimental verification.